The Influence of Lecturer Performance Evaluation on Improving the Quality of Learning at STKIP Harapan Bima - Syahrir, Syahrir; Fandir, A (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research examines the influence of lecturer performance evaluation on the quality of learning at STKIP Harapan Bima using quantitative and qualitative approaches. Data was collected through questionnaires from 200 students and in-depth interviews with lecturers and students. The research results show that 75% of students are satisfied with lecturers' performance, with an average satisfaction score of 4.2 out of 5. The quality of learning has increased, shown by 60% of students getting an A or B grade and 70% of students feeling an increase in the quality of learning after routine lecturer performance evaluations are carried out. Statistical analysis with Pearson correlation shows a significant positive correlation between lecturer performance evaluation and learning quality (r = 0.65, p < 0.01), with lecturer performance evaluation explaining 42% of the variability in learning quality (R² = 0.42). The most influential factor is the availability of lecturers for consultation. Perceptions of lecturers and students show that objective and constructive performance evaluations can increase lecturer motivation and, ultimately, the quality of learning. Research recommendations include implementing comprehensive and routine performance evaluations, using evaluation results for lecturer professional development, and further studies on specific factors and more extensive evaluation methods.